Enhancing customer satisfaction and loyalty through customer-defined market orientation and customer inspiration: a critical literature review - Mustafa R. Khan (Universiti Pendidikan Sultan Idris, 2018)
Enhancing customer satisfaction and loyalty through customer-defined market orientation and customer inspiration: a critical literature review by Mustafa R. Khan